2016
DOI: 10.1007/s11325-016-1321-4
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin protects the kidney against chronic intermittent hypoxia-induced injury through inhibiting endoplasmic reticulum stress

Abstract: Resveratrol, a polyphenol compound derived from various edible plants, protects against sepsis-induced acute kidney injury (AKI) via its anti-inflammatory activity, but the underlying mechanisms remain largely unknown. In this study, a rat model of sepsis was established by cecal ligation and puncture (CLP), 30 mg/kg resveratrol was intraperitoneally administrated immediately after the CLP operation. HK-2 cells treated by 1 μg/ml lipopolysaccharide, 0.2 μM tunicamycin, 2.5 mM irestatin 9389 and 20 μM resveratr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…In comparison, our study found that the level of oxidative stress increased in the kidney tissue in the CIH group. This finding is also in accordance with other reports that CIH caused the production of ROS (27 29). Wysocki et al.…”
Section: Discussionsupporting
confidence: 94%
“…In comparison, our study found that the level of oxidative stress increased in the kidney tissue in the CIH group. This finding is also in accordance with other reports that CIH caused the production of ROS (27 29). Wysocki et al.…”
Section: Discussionsupporting
confidence: 94%
“…Then, the tunicamycin‐induced increase in expression of UPR signaling molecules by ER stress was decreased by adiponectin in pLE cells. Results of previous studies also indicate inhibitory effects of adiponectin on ER stress in adipocytes (Liu et al, ), and cells of the liver (Jung et al, ), kidney (Ding et al, ), heart (Guo et al, ), and smooth muscle (Lu et al, ). These results indicate that adiponectin may prevent ER stress in uterine LE during early pregnancy.…”
Section: Discussionmentioning
confidence: 80%
“…Preservation of circulating adiponectin levels should be considered among the mechanism(s) contributing to the kidney-protective effect seen with EGFR inhibition. Adiponectin has been shown to be renoprotective in different kidney injury models and after podocyte injury (38,39). It protects against hypoxia-induced kidney injury by inhibiting endoplasmic reticulum stress (40).…”
Section: Discussionmentioning
confidence: 99%